Information Technology Framework for Pharmaceutical Supply Chain Demand Management: a Brazilian Case Study - Pedro Domingos Antoniolli (BBR: Brazilian Business Review)
The paper aims at proposing an information technology framework for demand management within a dyad on the supply chain pharmaceutical industry. The paper adopts the exploratory study as research method, involving a producer of generic drugs and its main distributor. Data was collected by semi - structured interviews. In pharmaceu tical supply chain, sharing information boosted by information technology translates into greater flexibility and reliability, lower costs, obtained through more reliable forecasting, and lower inventory requirements. There are few initiatives involving In formation Technology (IT) applied to demand management in pharmaceutical supply chains available in the literature. It was found that the IT framework proposed in this research is adherent to the demand management of the focused pharmaceutical dyad. Other assumption was that, if partners processes integration exist, better supply chain performance is achieved. It was found that, by means of proposed tools and solutions, such as RFID and involved partners applications integration, this goal could be achieved . Because of the chosen research approach, results may be restricted to these specific dyadic processes. Further application of the proposed IT framework have to be tested. The paper identifies demand management strategic and operational processes that can reach a better performance by using the proposed IT framework. Based on the literature, were identified which IT requirements should be met to demand management processes optimization. Additionally, were applied questionnaires and interviews to the focuse d dyad personnel, to corroborate the data identified in the literature. Answers found in the case study link literature elements with those stated by respondents. Finally, based on this, was conceived an IT framework composed of three elements: 1. One spec ific for infrastructure, to enable data and systems interoperability among SC participants, considering a virtualized infrastructure environment (Cloud); 2. An information system solution to integrate partners applications, based on the reference component model structure (CORBA / CCM – Common Object Request Broker Architectures / Corba Component Model); 3. One element responsible for logistics operations, formed by fourth and fifth pieces: a tool to streamline the logistics flow, and to obtain prompt inven tory data, provided by a RFID (Radio Frequency Identification) solution; and another to provide information about production and logistics lead times, applied to demand forecasts elaboration and to streamline the order fulfillmentprocess, based on OEE (Ov erall Equipment Effectiveness) solution. This paper covers a field that is not widely researched that is IT solution application into pharmaceutical demand management processes, and related performance improvements.